A 4-(1H-Benzo[d]oxazole-2-yl)-2-methoxyphenol as Dual Selective Sensor for Cyanide Ion Detection - Rahmawati, R.; Purwono, B.; Hadisaputra, S. (Asian Journal of Chemistry, 2019)
A dual sensor based on benzoxazole containing moiety S3 was successfully synthesized and applied for detection of CN− ion. The S3 molecule changed its colour for dark brown to dark green on addition of the CN− ion only in DMSO solvent. The limit of detection (LOD) and association constant (Kass) values was 0.4 × 10−6 M and 1.0 × 107 M−1; and 0.46 × 10−4 M and 1.0 × 105 M−1 determined by UV-visible spectroscopic titration and fluorescence titration, respectively.